Comparison of Kegel exercises and a combination of Kegel exercises with the use of the KegelSmart biofeedback device in the treatment of static urinary incontinence - Mirela Begić; Nedima Kapidžić-Bašić; Asja Hotić-Hadžiefendić; Asmir Konjić; Dragana Bojinović-Rodić; Igor Hudić (Medicinski glasnik, 2023)
Aim: To determine which of the two methods, Kegel exercises or combination of Kegel exercises with the use of the KegelSmart biofeedback device, has better therapeutic effects on the symptoms of SUI in females. Methods: Fifty female patients with SUI were randomly divided into two groups: 25 treated with Kegel exercises, and 25 with the combination of Kegel exercises with the use of the KegelSmart biofeedback device. Patients in both groups performed Kegel exercises 30 minutes daily for 30 days. Patients in the second group, in addition to Kegel exercises, applied the KegelSmart device intravaginally for 20 minutes daily for 30 days. All patients filled out a questionnaire based on 12 questions consisting of an objective and a subjective component. Results: The basic characteristics of the patients from both groups were not statistically significantly different: age 55.16 vs 54.52 years; number of births 1.80 vs 1.96; body mass index 29.12 vs 28.40. There was a statistically significant reduction in the values of all analysed objective and subjective parameters in the group treated with combination of Kegel exercises with the use of the KegelSmart biofeedback device compared to Kegel exercises group. Conclusion: Combination of Kegel exercises with the use of the KegelSmart biofeedback device has better therapeutic effects than Kegel exercises on the objective and subjective symptoms of SUI.
Keywords: female patients; Kegel exercise; pelvic floor muscles